Non-catalytic NOx reduction for marine Diesel engine: an experimental approach - Galletti Anna Maria Raspolli (EDP Sciences, 2021)
Recent legislation concerning air pollutant emissions from ships (Tier III) has considerably decreased NOx emission limits for recreational ships with less than 500 gross tonnages and greater than 24 m load line length (LLL), the so-called “large yachts”. For these yachts, which adopt multiple Diesel engines with maximum power ranging from 800 to 2000 kW, the new NOx limit is less than 2 g/kWh. To satisfy that limit, engine makers suggest the adoption of a classic SCR system with urea injection but this methodology, in addition to requiring a large space for installation, does not seem so appropriate for diesel engines of large yachts that normally operate at low power with exhaust temperatures often well below 300 °C, therefore not sufficient to allow the correct functioning of the SCR. The aforementioned circumstances have prompted Sanlorenzo Spa (La Spezia – Italy), one of the world’s leading companies in the production of pleasure boats, to collaborate with the University of Pisa in the study of alternative solutions to SCR systems. Recently there is a great interest in innovative NOx abatement systems, based on the possibility of absorbing NOx molecules into seawater through the utilization of appropriate aqueous solutions containing targeted saline oxidizing agents. The present study describes the first results of a research program aimed to identify, from one side, the best saline oxidizing agent for an aqueous NOx abatement and, from the other, the best washing methodology compatible with the propulsion layouts usually adopted on yachts. In the engine testing laboratories of the Department of Energy, Systems, Territory and Construction Engineering (DESTeC) of the University of Pisa, an experimental apparatus has been created to reproduce the real conditions of underwater engine exhausting. This device was combined with a small 1.2 L direct injection diesel engine. The first results showed a reduction of the NOx emissions of about 27% by using a gas washing with wet scrubber, followed by bubbling in water, using 0.2 molar NaClO saline solutions.